Working to Reduce Crime: Exploring the Link Between Economic Participation and Crime Rates in Forsyth County, N.C. Neighborhoods - Blizard, Zachary D. (Crime & delinquency, 2024)
We examine the relationship between economic participation rates and rates of assaults, vandalisms, and drug offenses in neighborhoods in Forsyth County, N.C. We use a unique dataset containing assault, vandalism, and drug offense rates at the neighborhood level from 2013 to 2020. We estimate a two-way fixed effects spatial Durbin regression model relating crime rates to economic participation rates for the three types of crime. The results show that neighborhoods, proxied with census tracts, with higher economic participation rates among its residents have significantly lower crime rates. The relationship exists even after controlling for unobserved heterogeneity and spatial autocorrelation. Workforce programs that recruit individuals from neighborhoods with low economic participation rates may have the additional benefit of reducing crime.